Challenges in Current Coral Reef Protection – Possible Impacts of UV Filters Used in Sunscreens, a Critical Review - Moeller, Mareen; Pawlowski, Sascha; Petersen-Thiery, Mechtild; Miller, Ingo B.; Nietzer, Samuel; Heisel-Sure, Yannik; Kellermann, Matthias Y.; Schupp, Peter J. (Frontiers in Marine Science, 2021)
Coral reefs are highly endangered ecosystems. The identification and quantification of potential stress factors are essential to protect them. UV filters from sunscreens that are introduced to coral reef areas are considered as one of these stressors. Their impacts on limnic organisms have also been shown to be highly variable. It is therefore to be expected that their effects on corals also differ significantly and that each compound has to be evaluated individually. The demand for conclusive benchmarks and guidelines from policy makers and the public over the past years show the necessity for an objective literature review on the effects of various UV filters on scleractinian corals. Here, we review the present literature, summarize the data on the different UV filters and discuss the different approaches, advantages and limitations of the studies. However, the methods used in the latter studies vary greatly. They differ in many aspects such as species and life stage used, field and laboratory approaches, with exposure times ranging from hours to weeks. Some studies include analytics and measure the actual test concentration, others only provide nominal concentrations. The lack of standardized methods renders comparisons between studies futile. Additionally, most UV filters have only been investigated in a single or a few studies of different quality. Reliable thresholds are therefore impossible to draw on the basis of currently available studies. Nevertheless, certain UV filters repeatedly showed comparable toxicity in both freshwater and marine species tested. Yet, existing differences in results from coral tests emphasize the need for a standardized testing method comparable to those established for other aquatic organisms in order to allow for a more conclusive assessment. In this review, we describe what a scientifically sound testing proposal should include in order to obtain reliable and reproducible data, which ultimately should result in an internationally organized standardized ring test trial. Such standardized toxicity tests would enable validation of coral toxicity data related to UV filters, but also testing of other types of compounds that are known to be introduced and affect coral reefs, thus helping to identify significant stressors and enabling objective policy decisions.